Desarrollo e implementación de un sistema para el control de inventarios en la empresa savreh s.a. de la cuidad de Latacunga, mediante el análisis de la metodología iconix - Casa Toapanta, Romel Santiago (2015)
The elaboration of the software in the “SAVREH” S.A. Company, in Latacunga city, has an important objective: to check whole the wine shop area through a special computer System, according the characteristics and conditions that are received the products that are used to make different heavy machines in order to pay attention the needs of the clients and the quality of the products. At present the processes are realized manually, but just with the modern technology, as the informatic sciences, we can digitalizer them. With the help through several sets of programming tools, such as the data base in order to store all kind of information about entrance and exit of products in the area of wine shop of SAVREH S.A. Company. In order to encrease the necessary information for the elaboration of the system we will use the molding languages according to requirements of the system, such as: how are entering data, their actualization, correction and necessary calculations. With these stages we will be establishing a modern system to manage the data about the company and specially of the wine shop on all movements of entrance and exit of products, through analysis of the ICONIX Methodology.